Does the evidence really suggest that we should completely revascularise bystander disease in patients with ST elevation myocardial infarction undergoing primary angioplasty? Why we still need more definitive trial data to change routine practice. (1st February 2017) - Mariathas, Mark; Olechowski, Bartosz; Mahmoudi, Michael; Curzen, Nick
ABSTRACT: Introduction : There remains considerable heterogeneity in the management of significant lesions in non culprit coronary arteries in STEMI patients undergoing primary percutaneous coronary intervention (PPCI). Three recent randomised trials have shown clinical outcome benefit in a complete revascularisation approach when compared to PPCI of the culprit artery alone. By contrast, observational data suggest that an aggressive complete revascularisation may not confer clinical benefit and may, in some cases, be harmful. Areas covered : In this review we discuss the three recent randomised trials that have advocated a complete revasculariation approach in addition to data available from registries. Expert commentary : An adequately powered, randomised controlled trial is required to answer the question of whether complete revascularisation in STEMI patients is beneficial and, if so, whether it should be ischaemia directed and whether it should be at the index procedure or staged.